Unveiling The Complex Relationship: Exploring The Connection Between Polygyny And Domestic Violence In India With Evidence From National Family Health Survey- 5 (Journal of Namibian Studies : History Politics Culture, 2023)
India saw the rise of domestic violence during the Covid period. However, domestic violence has been a long-existing historical nuisance for women in India and around the globe. One such practice which can be attributed towards the existing domestic violence scenario in India is polygyny. While polygyny is deeply rooted in certain religious and cultural beliefs, it has been scrutinised due to its potential association with domestic violence. Polygyny, although legally prohibited for most Indians under the Hindu Marriage Act of 1955, continues to exist as a customary practice in specific communities. While the prevalence of polygyny in India is challenging to ascertain due to its clandestine nature, it is more commonly observed in rural areas and among economically disadvantaged populations. Several factors contribute to the perpetuation of polygyny, including patriarchal norms, economic considerations, and social pressures. The association between polygyny and domestic violence has been the subject of extensive research and debate worldwide. However, there is very little research in this area conducted in India.This study aims to shed light on the complex relationship between polygyny and domestic violence in India, using multivariate and bivariate methods of secondary sources involving the evaluation of government reports and surveys. Also emphasizing the need for a nuanced understanding of the factors contributing towards this phenomenon. Finally, the study discusses the evaluation results sweeping aside any bias